2020
DOI: 10.3390/su12239930
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Adoption of Sustainable Cloud Computing Solutions

Abstract: The paper is dedicated to factors influencing users’ adoption of sustainable cloud computing solutions. The article covers the important characteristics related to cloud computing. It also discusses how sustainable cloud computing is important for sustainability. The current state of their security and potential threats waiting for users is reviewed. The purpose of this study is to investigate the influence of perceived usefulness, security, availability, and satisfaction on users’ adoption of sustainable clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…One of the definitions of perceived usefulness is that it is the degree to which an individual believes that using a particular system will improve performance [50]. However, it is better to say that using a given solution will affect the user's ability to use it to their advantage [51]. According to the consumer, the most important thing is the positive attitude of use to performance [52].…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…One of the definitions of perceived usefulness is that it is the degree to which an individual believes that using a particular system will improve performance [50]. However, it is better to say that using a given solution will affect the user's ability to use it to their advantage [51]. According to the consumer, the most important thing is the positive attitude of use to performance [52].…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Professional training initiatives may have an indirect influence on such a situation [18] since future users are familiarized with the advantages of the technology from the very beginning. One cannot also ignore the fact that informed users tend to place a high value on security and service availability [34]-both vital in the networking context.…”
Section: Discussionmentioning
confidence: 99%
“…More strictly technology-focused studies include contributions by Saprikis et al [31], Wild et al [32], Putri and Sucahyo [33], Pankowska et al [34], Alkawsi et al [35], as well as Macik [36]. As far as the former is concerned, the most significant determinants to employ augmented reality technologies are discussed, providing managers of shopping malls with the instruments to enhance customers' experiences, streamline the information flow to potential customers, and overhaul business models [31].…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Park and Kim [5] conducted research using the TAM and suggested that the perceived mobility, usability, connectivity, security, and service and system quality are the main variables affecting the intention to accept mobile cloud services. Pańkowska et al [6] also used the TAM model to study the factors influencing users' adoption of sustainable cloud computing solutions and suggested that perceived availability and security affect the perceived usability and system service quality, and both variables affect attitudes and usage.…”
Section: Cloud Computing Servicementioning
confidence: 99%